STRATEGI PEMBELAJARAN YANG MEMERDEKAKAN - Budiningsih, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Instructional Technology is very concerned in solving social life problems which occurs due to lack of human resources and/or social constraints in our community. Through its field of study, Instructional Technology provides services of learning sources and develops various instructional strategies as part of instructional design scopes to achieve desirable goals. Development of liberation instructional strategy is conducted in purpose of solving social problems by assuring children rights to undertake learning activities in accordance with their own personal characters. Liberation instructional strategy puts learners’ activeness as the most important factor in determining learning process and achievements. It enables learners to quickly and precisely acquire, master, work over, and develop the information in such a way that it would encourage the formation of creative and productive thinking habit.